Association between prognostic nutritional index and survival of patients with oral cancer: a meta-analysis - Jia, Guodong; Wang, Zhen (Frontiers in Oncology, 2025)
Oral cancer (OC) remains a major global health burden with unsatisfactory survival outcomes. The prognostic nutritional index (PNI), derived from serum albumin and lymphocyte counts, has been proposed as a simple biomarker of nutritional and immune status. This meta-analysis was performed to summarize the association between PNI and survival of patients with OC. We systematically searched PubMed, Embase, and Web of Science for longitudinal observational studies which compared low versus high PNI groups and reported hazard ratios (HRs) with 95% confidence intervals (CIs) for overall survival (OS) and/or progression-free survival (PFS). Pooled analyses were performed using random-effects models accounting for heterogeneity. A total of 16 cohorts were included. Low PNI was significantly associated with poorer OS (HR: 2.68, 95% CI: 2.00 to 3.58; I² = 64%) and PFS (HR: 1.99, 95% CI: 1.66 to 2.39; I² = 0%). Subgroup analyses revealed a stronger association in patients with mean age ≥ 65 years for both OS (HR: 3.49 vs. 1.48; p for subgroup difference = 0.001) and PFS (HR: 2.76 vs. 1.42; p = 0.002) as compared to those < 65 years. Meta-regression confirmed age as a significant source of heterogeneity (OS coefficient = 0.060, p = 0.004; adjusted R² = 81.4%; PFS coefficient = 0.055, p = 0.02; adjusted R² = 100.0%). Low PNI before treatment is associated with adverse survival in patients with OC, particularly in older populations. These findings support the integration of PNI into prognostic assessment in OC management.Systematic review registrationPROSPERO, identifier CRD420251139755.